Estiramiento Analítico en el Síndrome Miofascial del Hombro. Hospital Básico Dr. Publio Escobar. Colta 2018-2019 - Garcés García, Cinthya Elizabeth (2019)
This research work focused on determining the effectiveness of technique Analytical Stretching in Myofascial Shoulder Syndrome, a population between 20-40 years of Hospital Dr. Publio Escobar, which is located in the canton Colta For this research design field the same that allowed the collection information was applied, the observation technique was also employed as it allowed the collection of data and information for subsequent recording and analysis, the instruments used are clinical history, which has two tests such as Goniometry (measuring mobility ranges) and the EVA scale (pain assessment), for the processing and interpretation of the information the statistical software SPSS was used. The results obtained in this research showed that the gender with the highest incidence is the feminine with one (61.5%). The application time was four weeks, achieving a significant reduction in pain, from a moderate (46.2%) and intense (23, 1%) to no more prolonged pain in 100% of the population, at the level of Mobility ranges showed a significant increase in patients with functional mobility, inflection from 7.69% to 96.15% (150 0 -180 0), ranging from 38.5% to 100%(30 -45 ), in abduction from 1 1.53% to 92.30% (60 0-180 0), in adduction, internal and external rotation from 0% to 100%. Due to the temperature increase, and induction Vascularity to stretch, reflex produces periodic application of this technique.